Settlement of Default Disputes in Murabahah Agreements Through Mediation in the Perspective of Islamic Bond Law (Study of the Analysis of the Decision of the Banyumas Religious Court No. 1696/Pdt.G/2020/PA.Bms.) - Ramadhan, Aditya (International Journal of Social and Management Studies, 2023)
The dispute over default in the murabahah financing contract between the Sharia People's Financing Bank (BPRS) PT Bina Amanah Satria Purwokerto and its customers became one of the sharia economic cases tried by the Banyumas Religious Court. The customer has defaulted on the Murabahah financing contract Number 202/PRBH/II/2019 in the dispute. The purpose of this study is to examine the view of Islamic Binding Law on the settlement of default problems in murabahah contracts through mediation, as well as the legal force of the Judge's mediation conclusion. The method used includes library law research, namely research that focuses on the object of research in the form of Banyumas Religious Court Decision Number 1696/Pdt.G/2020/PA.Bms, through a case approach. And supported by secondary data and primary data. The results of this study indicate that the conflict resolution approach adopted in this case is the idea of mediation in Islamic law. Both legally and practically, especially about the use of the concept of sulh. Furthermore, the judge's decision to grant the settlement was based on the outcome of the mediation. When the parties to a peace agreement have indirectly implemented the terms of sulh, the court's decision to grant the peace is based on the outcome of the mediation. The requirements of the principles, pillars, and conditions of the peace agreement have implicitly applied the provisions of the agreement based on Islamic binding law. The peace deed in the decision of the Banyumas Religious Court Number 1696/Pdt.G/2020/PA.Bms is legally binding in perpetuity. A commentator judgment is a judgment that can be executed, namely a judgment containing an order.